2021
DOI: 10.1007/s00216-021-03377-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging point-of-care biosensors for rapid diagnosis of COVID-19: current progress, challenges, and future prospects

Abstract: Coronavirus disease 2019 (COVID-19) pandemic is currently a serious global health threat. While conventional laboratory tests such as quantitative real-time polymerase chain reaction (qPCR), serology tests, and chest computerized tomography (CT) scan allow diagnosis of COVID-19, these tests are time-consuming and laborious, and are limited in resource-limited settings or developing countries. Point-of-care (POC) biosensors such as chip-based and paper-based biosensors are typically rapid, portable, cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 209 publications
(228 reference statements)
0
66
0
Order By: Relevance
“…Another research group reported eCovSens, an antigenic COVID-19 sensor that detects the S1 protein on fluorine-doped tin oxide decorated with Au NPs or screen-printed carbon electrodes. A detection limit of 80 femtoMolar (fM) and 120 fM for the S1 protein on the FTO and SPCE, respectively, was achieved in saliva in 30 s [144][145][146][147].…”
Section: Electrochemical Biosensormentioning
confidence: 99%
“…Another research group reported eCovSens, an antigenic COVID-19 sensor that detects the S1 protein on fluorine-doped tin oxide decorated with Au NPs or screen-printed carbon electrodes. A detection limit of 80 femtoMolar (fM) and 120 fM for the S1 protein on the FTO and SPCE, respectively, was achieved in saliva in 30 s [144][145][146][147].…”
Section: Electrochemical Biosensormentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 18, 2021. ; https://doi.org/10.1101/2021.07.14.21260291 doi: medRxiv preprint friendly, Rapid and Robust, Equipment-free, Deliverable to end-users (ASSURED) diagnostic tool [20,21]. Thus, antigen testing has been a suitable tool for global monitoring of new SARS-CoV-2 cases.…”
Section: Specimen Sourcesmentioning
confidence: 99%
“…In early 2021, the DoD began using antigen testing on asymptomatic active duty and DoD civilian personnel [18,19]. Antigen tests meet the World Health Organization's (WHO) definition of an Affordable, Selective and Sensitive, User-friendly, Rapid and Robust, Equipment-free, Deliverable to end-users (ASSURED) diagnostic tool [20,21]. Thus, antigen testing has been a suitable tool for global monitoring of new SARS-CoV-2 cases.…”
Section: Specimen Sourcesmentioning
confidence: 99%
“…In recent years, significant advancements have been carried out in the development of smartphone-based chips, paper-based microfluidics, and miniature environmental monitoring systems (Hong et al 2018 ; Marquez et al 2019 ; Puangbanlang et al 2019 ; Nelis et al 2020 ; Fernández-Abedul 2021 ). The portable diagnostic test kits have been explored extensively in the healthcare sector and with pandemics like COVID-19, the requirements for accurate sample handling and analysis become even more crucial globally (Yang et al 2018 ; Kim et al 2019 ; Bhalla et al 2020 ; Ghosh et al 2020 ; Rasmi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%